Minocycline Increases in-vitro Cortical Neuronal Cell Survival after Laser Induced Axotomy - Yulug, Burak (Curr Clin Pharmacol, 2020)
BACKGROUND: Antibiotic therapies targeting multiple regenerative mechanisms have the potential for neuroprotective effects, but the diversity of experimental strategies and analyses of non-standardised therapeutic trials are challenging. In this respect, there are no cases of successful clinical application of such candidate molecules when it comes to human patients. METHODS: After 24 hours of culturing, three different minocycline (Sigma-Aldrich, M9511, Germany) concentrations (1 µM, 10 µM and 100 µM) were added to the primary cortical neurons 15 minutes before laser axotomy procedure in order to observe protective effect of minocycline in these dosages. RESULTS: Here, we have shown that minocycline exerted a significant neuroprotective effect at 1 and 100μM doses. Beyond confirming the neuroprotective effect of minocycline in a more standardised and advanced in-vitro trauma model, our findings could have important implications for future studies that concentrate on the translational block between animal and human studies. CONCLUSION: Such sophisticated approaches might also help to conquer the influence of human-made variabilities in critical experimental injury models. To the best of our knowledge, this is the first study showing that minocycline increases in-vitro neuronal cell survival after laser-axotomy.